The Influence of Government Expenditure in the Health Sector, Education Sector, Capital Expenditures on the Human Development Index in South Sulawesi Province - Dirmansyah Darwin; Madris; Fatmawati (Enrichment : Journal of Management, 2022)
This study aims to analyze the effect of government spending on health, government spending on education and capital spending on the Human Development Index through economic growth in South Sulawesi Province. The data used in this research is secondary data that comes from the Central Bureau of Statistics of South Sulawesi Province and the Directorate General of Fiscal Balance of the Republic of Indonesia. The analytical method used is a multiple linear regression analysis method using Cross Section and Time Series data for each district/city between 2011-2020. The research findings show that the variable government spending in the Health sector has a negative and significant effect on the Human Development Index in South Sulawesi Province, the two variables in government spending in the Education sector have a negative and significant effect on the Human Development Index in South Sulawesi Province, third, the capital expenditure variable does not effect on the Human Development Index in the province of South Sulawesi. The findings presented are a form of phenomenon where in increasing human capital, it is necessary for us to review the government expenditure system so that it can be more targeted in maximizing spending for the sake of increasing the human resources of society.